EFFICIENCY OF DRIP IRRIGATION IN THE CULTIVATION OF WINTER WHEAT IN THE CONDITIONS OF BARREN SOILS - A. Z. Artikov; S. M. Boltaev; O. Boynazarov (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the advantages of drip irrigation in the cultivation of winter wheat in the conditions of bald meadow soils of Surkhandarya region, moistening of the furrowed and subsoil layers of the soil with scattered roots, water consumption is reduced by 45-50% of the number of irrigations and seasonal water consumption, and nitrogen mineral fertilizers by 20-25%, and the yield of winter wheat grain increased by 4.9-6.5 ts.